Between defects and inclusions: The fate of tellurium in pyrite - Börner, Frederik; Keith, Manuel; Fougerouse, Denis; Macauley, Chandra; Felfer, Peter; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann (Chemical Geology, 2023)
Tellurium (Te) is a critical commodity, essential for renewable energy technologies and other high-tech applications. Most Te is currently recovered from anode slimes, i.e., waste arising from copper refining. Rising demand and the key role for the green transition make the diversification and extension of the Te supply important. However, the nature of Te incorporation into ores is still poorly understood and hinders their economic potential. Here, we investigate the distribution of Te in pyrite from a high-grade Au-Ag-Te epithermal-type ore, where pyrite is already processed for ‘invisible’ Au, to inform metallurgical extraction methods, and secure future Te supply. Current models of Te incorporation into pyrite suggest a solid-solution limit in relation to As, similar as for ‘invisible’ Au. In this study, we identified three distinct modes of Te incorporation in pyrite, which challenge previous solubility models: (1) Te solid-solution, at concentrations (up to 285 ppma) that significantly exceed the previously suggested solubility limit. (2) Nano-telluride inclusions along cracks that formed by intra-grain remobilization. (3) Crystal defects, enriched in Te through pipe diffusion hosting up to 0.5 at. % Te. Our results therefore provide new fundamental insights into the chemical and structural coordination of Te in pyrite, which may guide future efforts for its direct recovery.<br
Keywords: Pyrite; Tellurium (Te); Atom probe tomography (APT); Low sulfidation epithermal; Solid solution; Inclusions; Defects; Vatukoula